Analysis of the phenomenon of college students’ “delayed employment” under the background of accelerating the construction of an education powerhouse and research on countermeasures - Yuan Renhui; Chen Hongcui; Tian Shengwen (ITM Web of Conferences, 2025)
In the new era, the Party and the state are required to accelerate the construction of a powerful country in education, improve the quality of personnel training, and promote the high-quality development of the economic industries. However, contemporary college students generally exist the phenomena of "delayed employment", "non-employment" and "difficult employment", which is not conducive to the service of university personnel training for regional economic and industrial development, and is not conducive to the industry innovation and sustainable development to provide intellectual support and human resources guarantee. In this regard, based on the social background of accelerating the construction of education power, this study comprehensively and deeply analyzes the phenomenon of "delayed employment" among college students, and puts forward practical strategies for education departments, local colleges and universities, social enterprises and other entities to jointly solve the problem of college students' employment and entrepreneurship, so as to effectively help college graduates achieve high-quality full employment.